2016
DOI: 10.1080/13562517.2016.1141288
|View full text |Cite
|
Sign up to set email alerts
|

Learning through personal connections: cogenerative dialogues in synchronous virtual spaces

Abstract: This study describes the role of cogenerative dialogues in a synchronous virtual classroom. Cogenerative dialogues are a way for students and instructors to reflect upon in-class events and work collaboratively during the course to optimize teaching and learning. In the present study, cogen has been found to be a tool for enhancing connections among graduate students in the class leading to a reported increase of motivation and engagement. Cogenerative dialogues were essential in shifting responsibilities so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Garrison et al (1999) described e-learning in the context of a community of learners who are not bound by time or place, as with traditional classroom instruction, but who relied on computer-mediated interaction to facilitate the process of learning. Interaction in the online learning environment, not only involves the exchange of information intended to increase or reinforce knowledge development within the context of the course, it also actively encourages dialogue which leads to individual knowledge construction (Bondi, Daher, Holland, Smith, & Dam, 2016). Garrison et al (1999Garrison et al ( , 2001) argued that it is through this interaction that a community of learning is created and sustained, and that it is within the "community of inquiry" that critical thinking is developed and learning results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Garrison et al (1999) described e-learning in the context of a community of learners who are not bound by time or place, as with traditional classroom instruction, but who relied on computer-mediated interaction to facilitate the process of learning. Interaction in the online learning environment, not only involves the exchange of information intended to increase or reinforce knowledge development within the context of the course, it also actively encourages dialogue which leads to individual knowledge construction (Bondi, Daher, Holland, Smith, & Dam, 2016). Garrison et al (1999Garrison et al ( , 2001) argued that it is through this interaction that a community of learning is created and sustained, and that it is within the "community of inquiry" that critical thinking is developed and learning results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Four types of interaction have been identified in online tutorials: 'learner to interface', 'learner to content', 'learner to teacher', and 'learner to learner' (Martin, Parker, and Deale 2012). Studies with postgraduate students have found that students value peer interaction and experiences of community (Bondi et al 2016;Hokanson et al 2019). A survey of 1056 adults with experience of online learning in multiple contexts in the USA found lack of interaction was the biggest barrier to learning online (Muilenburg and Berge 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…learning the piano [26] and physical education assessments [27]. Involving learners in "cogenerating" some of their own learning in synchronous virtual environments fosters the development of personal connections and improves engagement [28]. This idea has parallels with the role of peer support in pain management programmes and merits further research.…”
Section: Research Implicationsmentioning
confidence: 99%